Systematic literature review on optimizing organizational culture and competencies in improving employee performance - Selviyanti, Nur Hidayah; Anshori, Mochammad Isa; Andriani, Nurita (Enrichment : Journal of Management, 2023)
The purpose of this study is to describe the relationship between organizational culture and competence to employee performance and to develop an optimal employee performance improvement model. Low employee performance is caused by low organizational commitment, namely employees do not obey all the rules set in the organization, ignore the commitment to always be part of the organization and do not pay serious attention to maintaining the success that has been achieved. Research using the SLR approach in journals published from 2020 to 2023. Solutions to overcome the optimization of organizational culture and human resource competencies, namely; 1) Carry out recruitment, selection and placement of human resources correctly according to their job desks or skills or skills in accordance with the initial to final stages, namely starting from Administrative Selection, Interview tests, Written tests, Physicotes, Follow-up interviews with the Director, Medical tests 2) Paying close attention when recruiting employees must be truly competent both in terms of theoretical or practical. 3) Increase the role of universities to provide competent human resources and be supported by the government as a policy maker. 4) Improve the competence of human resources by increasing their theoretical and practical aspects.